2000
DOI: 10.1136/thorax.55.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Airway neutrophilia in stable and bronchiolitis obliterans syndrome patients following lung transplantation

Abstract: Results-Compared with controls, airway wall neutrophilia was increased in both stable lung transplant recipients and those with BOS (p<0.05). BAL neutrophils and IL-8 levels were also increased in both groups of transplant recipients compared with controls (p<0.01), the levels being significantly higher in the BOS group (p<0.01). Neutrophil numbers in the lung parenchyma were not significantly diVerent between the two groups of lung transplant recipients. Conclusion-Increased levels of neutrophils are present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 25 publications
6
103
3
Order By: Relevance
“…This view is supported by findings in several animal (4,5) and clinical studies (6)(7)(8)(9)(10)(11)(12)(13). During lung transplant surgery, donor and recipient airways are anastomosed at the site of the left and right main bronchi.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…This view is supported by findings in several animal (4,5) and clinical studies (6)(7)(8)(9)(10)(11)(12)(13). During lung transplant surgery, donor and recipient airways are anastomosed at the site of the left and right main bronchi.…”
Section: Introductionsupporting
confidence: 72%
“…In contrast to Zheng et al (6), who reported an increased neutrophilia in donor airway walls of both patients suffering from BOS and stable patients compared to normal controls, we did not find a significant difference in airway neutrophilia between allogeneic and autologous airways in BOS patients. However, in stable patients we also found more neutrophils in allogeneic compared to autologous airways ( Figure 3).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…61,93,101 Neutrophilia is also prominent finding in several forms of immune-mediated lung injury including acute respiratory distress syndrome (ARDS) and in bronchiolitis obliterans syndrome (BOS), characteristic of lung allograft rejection. [102][103][104][105][106][107] PMN products such as elastase, myeloperoxidase, metalloproteinases and oxidants are abundant in the BAL fluid of patients with ARDS and are believed to contribute to the endothelial and epithelial damage that occurs in this setting. 102,107 Furthermore, increases in PMN activation markers may also be early indicators of BOS after lung transplant.…”
Section: The Role Of Neutrophils/polymorphonuclear (Pmn) Cellsmentioning
confidence: 99%
“…36,37 However, in this study, Aspergillus colonized cases who developed CLAD did not have a greater proportion of BAL neutrophils than those who remained CLAD free. 40 Collectively, this suggests further exploration of the role for CHIT1 and CHI3L1 in pathogenesis of CLAD is warranted.…”
Section: Discussionmentioning
confidence: 40%